The Yada Yada Prayer Group gets tough - Jackson, Neta. (Nashville : Thomas Nelson, 2005)
"The Yada Yada Prayer Group has been together for a whole year and so many good things are happening. However that's just when the Enemy knows to attack. The Yada Yada sisters realize they need to get tough"--Provided by publisher.
Keywords: Women -- Illinois -- Fiction; Christian women -- Fiction; Female friendship -- Fiction; Prayer groups -- Fiction; Chicago (Ill.) -- Fiction; Christian fiction